Lifetimes of image-potential states on Cu(100) and Ag(100) measured by femtosecond time-resolved two-photon photoemission - Shumay, Igor; Höfer, Ulrich; Reuss, Christian; Thomann, Ulrich; Wallauer, Wolfgang; Fauster, Thomas (Physical Review B, 1998)
We report time-resolved studies of image-potential stales on Cu(100) and Ag(100). Femtosecond ultraviolet-pump and infrared-probe techniques combined with two-photon photoemission have been used to measure relaxation dynamics of n = 1, 2, and 3 image-potential states. We found the lifetimes of these states on Cu(100) at room temperature to be 40+/-6, 120+/-15, and 300+/-20 fs, respectively. The corresponding values for Ag(100) are 55+/-5, 160+/-10, and 360+/-15 fs. [S0163-1829(98)06643-0].